Awareness on the use of veterinary drugs in the region of Sjenica as potential environmental pollutants - Ćurčić, Marijana; Ćatović, Rialda; Ćirović, Tatjana; Stojilković, Nikola; Buha Djordjević, Aleksandra; Antonijević Miljaković, Evica; Djukić-Ćosić, Danijela; Javorac, Dragana; Baralić, Katarina; Bulat, Zorica; Antonijević, Biljana (Archives of Pharmacy, 2022)
The aim of this study was to evaluate the awareness of livestock breeders on the used veterinary drugs in order to assess potential environmental contamination in the region of Sjenica. Veterinary drugs can enter the environment mostly due to widespread usage, but also as metabolites eliminated from the organisms. In order to evaluate the awareness of livestock breeders, a survey questionnaire was used. Questions were related to the most frequently used veterinary drugs without the supervision of a veterinary medical doctor. The obtained data show that the awareness of domestic animal breeders on the use of veterinary drugs is very low in the region of Sjenica. The most commonly used veterinary medicines were antibiotics, streptomycin, and benzylpenicillin-procaine, antihelmintic, albendazole. Unexpectedly, the animal breeders identified formaldehyde as veterinary medicine and used it as a disinfectant in poultry raising. The results also show that breeders frequently treat animals with drugs on their own, without control by veterinary medical doctors. Because of the wide use of veterinary medicines in the region of Sjenica, it monitoring of the environmental concentration of streptomycin, benzylpenicillin-procaine, and albendazole, as well as metabolites in soil and water should be recommended. Moreover, human exposure to these veterinary medicines could occur because of the abuse of veterinary medicines, no consultations with veterinary medical doctors, and non-proper handling of waste from animals.